Consumo de alcohol y su relación con la violencia familiar, Estudio de casos reportados en la comisaría de la mujer del Distrito de Tarapoto, periodo 2013- 2014 - Garrido Flores, Lucia (2016)
This study aimed to determine the relationship between domestic violence and alcohol consumption, as reported in the Commissariat for Women Tarapoto district during the period 2013 and 2014 a correlational descriptive research was conducted, cases cross with prospective data collection. The population consisted of 972 reported cases of family violence. Are 490 cases in 2013 and 482 in 2014. The sample consisted of 100% of the population who met the inclusion and exclusión criteria. The results achieved in the inferential analysis were 89.6% (871) of the complainant population are female; 34.0% (330) ranges from 19 to 29 years. 97.3% (946) lives in the city of Tarapoto. 60.4% (587) of the attacks were carried out by the spouse, followed by former partners in 18.9% (184). The overall proportion of alcohol consumption was 81.8%, with 89.0% (436) in 2013 and 74.5% (359) in 2014. The level of alcohol in blood of the aggressors of the cases reported in 2013 and 2014 was 48.9% from 0.001 to 0.500 grs./dl for subclinical normal and 32.0% from 0.501 to 2.000 g / dl for drunkenness. The predominant type of family violence was psychological violence in 40.4% (393), physical violence in 33.7% (328). In conclusion: there is statistically significant relationship between domestic violence and alcohol consumption in 2014 (p <0.05). No statistical relationship is reported in the 2013 period (p> 0.05).